Evaluation of the implementation of a Just-in-Time System for raw material inventory to satisfy production requirements - Prasetio, Alvin Agus; Tunjang, Hansly (JSM: Jurnal Sains Manajemen, 2024)
This study aimed to investigate the adoption of the Just In Time (JIT) system at Indu Kuh Coffee Palangka Raya. This study employs a descriptive research design with a quantitative approach, specifically utilizing a case study methodology. Data is collected from the organization’s research and analyzed using the Just In Time system method. Conclusions can be derived from the research results, which will then be utilized as a basis for decision-making to address a problem inside the firm. The research findings indicate that the company will suffer a total inventory cost of Rp. 3,072,847 if it adopts the Just In Time (JIT) strategy. This expense is significantly more cost-effective than the inventory expenses incurred by the company, totaling Rp. 4,640,000. Indu Kuh Coffee can save costs and reduce raw material inventory expenses by up to Rp1,567,847 by implementing the Just In Time (JIT) method